GAYA BELAJAR MAHASISWA PADA MATA KULIAH BAHASA JEPANG BERBASIS ONLINE LEARNING - Sri Muryati; Bekti Setio Astuti; Trismanto Trismanto (Jurnal CULTURE (Culture, Language, and Literature Review), 2021)
This research is predicated on the problem of learning that is faced by students in university during social distancing due to Coronavirus outbreak. One of the striking problems is most students are not comfortable with e-learning. The aim of this article is grasping the typology of students particularly in e-learning that is conjunction with four aspects namely learning patterns, doing assignments, learning habits and using tools. Furthermore, the other objective is the research will be contributed to lecturers, faculties, universities and policymakers in term of planning, creating, and developing e-learning systems. The methodology used in this research is quantitative with descriptive type where is the population  or sample as the object of the research and it is only to describe a variable without comparing to other variables. The result of the study denotes the typology of visual learners dominating learning pattern and doing assignment which was 54% and 46% respectively. While in learning habit, the auditory type was the most popular which was 42% however the kinesthetic type had a low percentage because this activity was rarely carried out in e-learning hence that is why the quantity is negligible.